Analysis of students' difficulties in understanding triangular material - Musfiratul, Musfiratul; Ikhsan, M.; Anwar, Anwar; Arijuddin, Arijuddin (International Journal of Trends in Mathematics Education Research, 2023)
This study aims to describe the difficulties experienced by students in understanding triangular material and the causes of these difficulties. This research is a descriptive research on 7 subjects selected from 23 grade VIII students at MTsS Darul Ihsan, Aceh Besar. The subjects of the study were selected based on the data of the test results of students' ability to solve triangular problems. Based on the test result data, subjects were categorized based on indicators of triangular material then in theinterview to dig deeper into the causes of students' difficulties. The interview results are transcribed and then analyzed qualitatively through the stages of data reduction, data presentation, and conclusion withdrawal. To ensure the validity of the data, a source riangulation is carried out, which compares data from interviews between students and teachers. The results showed that based on the achievement indicators of triangular material, the majority of students experienced conceptual difficulties compared to principle and procedural difficulties. The causes of difficulties experienced by students include: lack of focus during the learning process; lack of understanding of prerequisite material; lack of practice of varied questions; the teacher's explanation regarding the material cannot be easily understood by students; Lack of accuracy in understanding the meaning of the problem and Kurang careful in doing calculations.